2015
DOI: 10.1371/journal.pone.0130926
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng Berry Extract Promotes Maturation of Mouse Dendritic Cells

Abstract: Ginseng extract has been shown to possess certain anti-virus, anti-tumor and immune-activating effects. However, the immunostimulatory effect of ginseng berry extract (GB) has been less well characterized. In this study, we investigated the effect of GB on the activation of mouse dendritic cells (DCs) in vitro and in vivo. GB treatment induced up-regulation of co-stimulatory molecules in bone marrow-derived DCs (BMDCs). Interestingly, GB induced a higher degree of co-stimulatory molecule up-regulation than gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…7 GB has been reported to possess antioxidation, anti-inflammation, collagen synthesis facilitation, skin wrinkle care, whitening, moisturizing, skin barrier improvement, and atopy alleviation effects. 8 The growing studies of GBs seem to point to their health benefits in skin treatments. Among all the biological effects of GBE on skin, protective effects against photoaging and collagen synthesis are of remarkable importance.…”
Section: Introductionmentioning
confidence: 99%
“…7 GB has been reported to possess antioxidation, anti-inflammation, collagen synthesis facilitation, skin wrinkle care, whitening, moisturizing, skin barrier improvement, and atopy alleviation effects. 8 The growing studies of GBs seem to point to their health benefits in skin treatments. Among all the biological effects of GBE on skin, protective effects against photoaging and collagen synthesis are of remarkable importance.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-cancer activity: Recent studies have reported that the ginseng berry exhibits anti-cancer activity in in vitro [20][21][22][23][24][25] and in vivo [26,27], as well as the ability to attenuate chemotherapy-induced side effects [28,29]; these effects result from the promotion of dendritic cell maturation. Interestingly, the ginseng berry induced a higher degree of co-stimulatory molecule up regulation than the root extract at the same concentrations [30]. These studies indicate that the ginseng berry is an intense tumor therapeutic vaccine adjuvant that can be used in investigations and clinical research.…”
Section: Anti-diabetic Activitymentioning
confidence: 74%
“…Recent studies have reported that the ginseng berry also exhibits anti-cancer activity in in vitro [2, [73][74][75][76][77] and in vivo [2, 78,79], as well as the ability to attenuate chemotherapy-induced side effects [80,81]; these effects result from the promotion of dendrite cell maturation. Interestingly, the ginseng berry induced a higher degree of co-stimulatory molecule up regulation than the root extract at the same concentrations [82]. These studies indicate that the ginseng berry is an intense tumor therapeutic vaccine adjuvant that can be used in investigations and clinical research.…”
Section: Anti-cancer Activitymentioning
confidence: 74%